Loving-Kindness in Theravada Buddhism Scriptures - Kittiwanno, Phrapalad Wuthiphong (Journal of Thammawat, 2020)
Loving-Kindness in Theravāda Buddhism Scriptures means the spread and the cultivation of love with the equal minds in all living beings. There are 3 ways of expression of Loving-Kindness, namely :- 1) the spread and the cultivation of love in action 2) the spread and the cultivation of love in words 3) the spread and the cultivation of love in thought. The Buddha emphatically told human beings to have Loving-Kindness in animals and He also told human beings to have the view that all living beings are equal. The Buddha prescribed a model for the human beings to follow and taught how to use and spread Loving-Kindness by letting ourselves to live on the good base in all actions; good conduct in words and good conduct in thought. The Loving-Kindness that sustains the world is a principle which causes the human beings and animals to live together happily. It is also considered as the crux of Buddhism to reach the heavens and Nirvāna.